Significance of Serum Uric Acid and Lactate Dehydrogenase as An Indicator of Severity in Acute Amyloid Leukemia - Tauseef, Mahroze; Basat, Mehran; Rahim, Saadia; Kiani, Amber Nawaz; Wajid, Abeera; Asghar, Hafiz Muhammad; Tauseef, Mehreen (Indus Journal of Bioscience Research, 2025)
Objective: To estimate the serum level of uric acid in severe acute amyloid leukemia and to measure the high lactate dehydrogenase levels contributing in severity of acute amyloid leukemia. Study Type: It was Cross Sectional comparative study. Methodology: Out of 90 individuals of age 5 to 15 years, the mean age of participants in group A, group B, and group C was 10.53 ± 2.5, 10.5 ± 2.47 and 10.13 ± 2.501 respectively in Sheikh Zaid Hospital Lahore and Mayo Hospital Lahore. Blood uric acid and lactate dehydrogenase was evaluated by standard techniques spectrophotometer in the laboratory. All data collected was subjected to SPSS version 23. A relationship of serum uric acid and lactate dehydrogenase was calculated to see their significance in predicting the severity of disease subjected to statistical analysis. The quantitative variables like age were presented as mean ± SD. Prevalence was analyzed by Anova test, f value ≤ 0.005 will be taken as significant. Results: In Group A, 43.3% were males and 56.7% females, with a mean age of 10.53 years. Group B had 46.7% males and 53.3% females, with a mean age of 10.50 years, while Group C had 46.7% males and 53.3% females, with a mean age of 10.13 years. Significant differences were observed in uric acid, LDH, and WBC levels among the groups (p = 0.000). The ANOVA test confirmed a strong association among all groups. Conclusion: In conclusion, monitoring serum uric acid, LDH levels and WBC count is crucial in assessing the prognosis and mortality risk in patients with acute leukemia, particularly AML. Elevated LDH levels serve as a valuable prognostic indicator, especially in guiding treatment decisions and risk assessment for leukemic candidates.